2001
DOI: 10.1177/030089160108700603
|View full text |Cite
|
Sign up to set email alerts
|

Physical Impairment and Social Life, Goals among Adult Long-term Survivors of Childhood Cancer: A Population-based Study from the Childhood Cancer Registry of Piedmont, Italy

Abstract: Our study shows a good social adjustment of adult survivors from childhood cancer, with the exception of central nervous system tumors. From the methodologic point of view, the present study shows the feasibility of surveillance surveys on health-related quality of life with the contribution of general practitioners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
36
1
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 27 publications
6
36
1
2
Order By: Relevance
“…Cranial radiotherapy is known to be a strong risk factor for reduced educational attainment (Kelaghan et al, 1988;Haupt et al, 1994;Pastore et al, 2001;Langeveld et al, 2003;Mitby et al, 2003).This was reflected in our study by the better educational attainment level after infratentorial nonmedulloblastomas, probably treated with surgery only, in contrast to survivors of other brain tumours, who were more likely to have been treated with cranial radiotherapy. However, an internal comparison did not reach significance, which could be due to the analyses being based on small numbers in relation to this rather infrequent event.…”
Section: Discussionmentioning
confidence: 57%
See 4 more Smart Citations
“…Cranial radiotherapy is known to be a strong risk factor for reduced educational attainment (Kelaghan et al, 1988;Haupt et al, 1994;Pastore et al, 2001;Langeveld et al, 2003;Mitby et al, 2003).This was reflected in our study by the better educational attainment level after infratentorial nonmedulloblastomas, probably treated with surgery only, in contrast to survivors of other brain tumours, who were more likely to have been treated with cranial radiotherapy. However, an internal comparison did not reach significance, which could be due to the analyses being based on small numbers in relation to this rather infrequent event.…”
Section: Discussionmentioning
confidence: 57%
“…Thus, in our study, support from well-educated parents tended to increase the probability of achieving the highest educational levels. Another study also found that the educational level of survivors of non-CNS tumours exceeded that of the general population (Pastore et al, 2001), and childhood cancer survivors have been described as more mature, with greater appreciation of parental support, than healthy controls (Maggiolini et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations